Reconstruction of Advocate Policy in Assisting Child Cases Based on Value of Justice (A Study in Kuningan District) - Diding Rahmat; Teguh Prasetyo; Sri Endah Wahyuningsih (UNIFIKASI : Jurnal Ilmu Hukum, 2018)
An advocate is a person whose profession is providing legal services both inside and outside the court that meets the requirements based on legislations. In child cases, the role of advocates is needed to provide legal protection for children in order to create a child generation which is free from discrimination, violence and exploitation. The purpose of this research is to analyze various regulations regarding advocate policy in legal assistance on criminal cases, especially on child cases and how the policy is implemented in assisting child cases at the level of investigations in police, prosecutors office and court in Kuningan District. The method used in this research was the Evaluative Analysis method, which is a method of collecting and presenting the obtained data to analyze actual situation and subsequently carry out rational analysis based on juridical references through library and field research. As results, this research found that the regulations applied in providing legal assistance on child cases include; Article 23 paragraph (1) of Law Number 11 of 2012 concerning System of Child Criminal Justice, and Kuningan District Regulation Article 17 Point (b) Number 15 of 2003 concerning Implementation of Child Protection. Moreover, the implementation of advocate policy in assisting child cases in Indonesia has not been carried out optimally both in police, prosecutor's office and court due to the following factors, namely legislation factors, legal apparatus factors, and society awareness factors (legal culture). Therefore, there is a need for reconstruction of legal awareness through education, training and socialization, especially for the law enforcement of child cases. Besides, the societys legal culture regarding the obligation of advocate assistance needs to be improved so that the objectives to provide child protection can be achieved.Advokat adalah orang yang berprofesi memberi jasa hukum baik didalam maupun di luar pengadilan yang memenuhi persyaratan berdasarkan peraturan per Undang Undang. Dalam perkara anak peran advokat sangat di perlukan dalam perlindungan hukum bagi anak yang merupakan bagian terpenting dalam menjaga generasi anak yang bebas dari diskriminasi, kekerasan dan eksploitasi sehingga mampu membangun generasi anak bahagia dan sejahtera. Tujuan penelitian ini adalah untuk mengetahui perbagai peraturan mengenai kebijakan advokat dalam pendampingan hukum dalam perkara pidana khususnya terhadap terhadap perkara anak serta bagaimana implementasi kebijakan peran advokat dalam pendampingan perkara anak di tingkat penyelidikan dan penyidikan di kepolisisan, kejaksaan dan pengadilan Negeri Kuningan. Methode penelitian yang digunakan oleh penyusun dalam pembahasan penelitian ini adalah methode Evaluatif Analisis, yaitu suatu methode mengumpulkan dan menyajikan data yang diperoleh untuk menganalisis keadaan yang sebenarnya dan selanjutnya dilakukan analisis rasional berdasarkan acuan yuridis melalui penelitian kepustakaan dan penelitian lapangan. Hasil Penelitian ini yaitu Pertama,.Pasal 23 ayat (1) Undang Undang nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak, Perda Kabupaten Kuningan Pasal 17 hurp (b) No.15 Tahun 2003 Tentang Penyelenggaraan Perlindungan Anak .Kedua, Implementasi peran advokat dalam pendampingan perkara anak di Indonesia belum dilaksanakan dengan maksimal baik di kepolisian, kejaksaan maupun pengadilan hal ini karena faktor faktor sebagai berikut yaitu Faktor Peratuan Perundang Undangan, Faktor Aparat Hukum dan Faktor Kesadaran Masyarakat (Budaya Hukum). Oleh sebab itu perlu adanya rekontruksi peningkatan kesadaran melalui pendidikan, pelatihan dan sosialisasi terhadap penegak hukum perkara anak maupun terhadap budaya hukum masyarakat tentang kewajiban pendampingan advokat sehinga tujuan keadilan perlindungan anak dapat terpenuhi.